ANTECENDENT FACTORS YANG BERPENGARUH TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA ORGANISASI - Ketut Sudarma (Manajemen dan Bisnis, 2013)
The organizational performance has not achieved its optimum yet in Private Higher Education inCentral Java due to several factors both the external factors and internal factors. The externalfactors are intense competition going on competition is among private university itself,competition with State University, as well as the possibility of competition with foreignuniversities. The internal factors are derived from the behavior of its own human resources, suchas the tendency of low organizational commitment, ineffective leadership, organizational cultureand career development that is not performing well. The purposes of this study are to describethe organizational culture, transformational leadership, career development, organizationalcommitment and organizational performance, to analyze the influence organization culture,transformational leadership and career development on organizational commitment andorganizational performance, to analyze the influence of organizational culture, transformationalleadership and career development to organizational performance through organizationalcommitment. The study population numbered 396 head of course. Sample of 130 respondentsassigned, according to recommendation of Hair, et al. (1998) that the sample for SEM analysisbetween 100-200 respondents. The data analysis is using SEM (Structural Equation Modelling).The results of this study show that organizational culture, transformational leadership and careerdevelopment are statistically positive and significant impact on organizational commitment; andorganizational performance. Organizational commitment mediates the effect of organizationalculture, transformational leadership and career development to organizational performance.Thus, organizational commitment is very important and needs to be improved as early aspossible so that human resources in universities in Central Java have better responsibility andloyalty to their institutions.Belum maksimalnya kinerja organisasi pada Perguruan Tinggi Swasta di Jawa Tengahdisebabkan oleh beberapa faktor di antaranya adalah faktor eksternal dan faktor internal. Faktoreksternal yaitu ketatnya persaingan yang terjadi, yakni persaingan antar Perguruan Tinggi Swastasendiri, persaingan dengan Perguruan Tinggi Negeri, maupun kemungkinan persaingan denganperguruan tinggi asing. Faktor internal yaitu bersumber dari perilaku sumber daya manusiasendiri, seperti kecenderungan rendahnya komitmen organisasional, kepemimpinan belumberjalan efektif, budaya organisasi dan pengembangan karir belum terlaksana denganbaik.Tujuan penelitian ini adalah: mendiskripsikan budaya organisasi, kepemimpinantransformasional, pengembangan karir, komitmen organisasional dan kinerja organisasi,menganalisis pengaruh budaya organisasi, kepemimpinan transformasional, penegembangankarir terhadap komitmen organisasional dan kinerja organisasi, serta menganalisis pengaruhbudaya organisasi, kepemimpinan transformasional, pengembangan karir terhadap kinerjaorganisasi melalui komitmen organisasional. Populasi penelitian berjumlah 396 ketua programstudi. Sampel ditetapkan 130 responden, sesuai rekomendasi Hair, et al. (1998) bahwa sampeluntuk analisis SEM antara 100-200 responden. Analisis data menggunakan SEM (StructuralEquation Modeling). Hasil penelitian menunjukkan bahwa budaya organisasi, kepemimpinantransformasional dan pengembangan karir berpengaruh positif dan signifikan terhadap komitmen organisasional dan kinerja organisasi. Komitmen organisasional memediasi pengaruh budayaorganisasi, kepemimpinan transformasional dan pengembangan karir terhadap kinerja organisasi.Dengan demikian membangun komitmen organisasional sangat penting dan perlu dilakukansedini mungkin agar SDM di Perguruan Tinggi Swasta Jawa Tengah mempunyai tanggungjawab dan loyal terhadap lembaga dan tidak mudah meninggalkan lembaganya sehingga kinerjaorganisasi dapat meningkat.